2001
DOI: 10.1021/es0010305
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gasoline Formulation on Methyl tert-Butyl Ether (MTBE) Contamination in Private Wells near Gasoline Stations

Abstract: MTBE concentrations ranged from <1.0 micro/L (microg/L) to 61 microg/L, with a mean of 12.0 microg/L. MTBE contamination of > or =1 microg/L was detected more frequently in case wells (28%) than control wells (5%) (p = 0.015). MTBE contamination of > or =1 microg/L occurred more frequently in private wells near facilities selling oxygenated gasoline (38%) than private wells near facilities selling conventional gasoline (20%) (p = 0.11). Statistical significance may have been achieved with a larger sample size.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Because it has no other uses, its presence indicates contamination by gasoline; its concentrations are higher in wells near gasoline stations and particularly high near gasoline stations that sell oxygenated fuel. 22 MTBE is toxic and carcinogenic in experimental animals 23 and is now banned in most states. Ethanol will likely replace MTBE entirely for oxygenating fuel.…”
Section: Methyl Tertiary Butyl Ethermentioning
confidence: 99%
“…Because it has no other uses, its presence indicates contamination by gasoline; its concentrations are higher in wells near gasoline stations and particularly high near gasoline stations that sell oxygenated fuel. 22 MTBE is toxic and carcinogenic in experimental animals 23 and is now banned in most states. Ethanol will likely replace MTBE entirely for oxygenating fuel.…”
Section: Methyl Tertiary Butyl Ethermentioning
confidence: 99%
“…TBA is common MTBE hydrolysis and biodegradation product. As regards that MTBE biodegradation reaction has to be conducted by specific strain in an aerobic condition, which such a condition isn't available in underground water, therefore, TBA can not be formed as a result of MTBE biodegradation [8] . It seems that, aluminosilicate compounds in the earth layers can catalyze the MTBE hydrolysis reaction in a long term period.…”
Section: Resultsmentioning
confidence: 99%
“…A modeling research has indicated that MTBE plume lengths will extend in the coming years hence significant numbers of MTBE release accidents may continue to reveal this contaminant as problematic source of contamination for the environment as of the year of 2010 [7,8] . Investigation conducted by a Blue Ribbon Panel of the USEPA, reported that MTBE concentration in approximately 1% of drinking water supplies exceeded 20 ppb [9] .…”
Section: Introductionmentioning
confidence: 99%
“…This article documents the application of a low-cost, expedient, scalable UVP system that has been successfully applied at a gasoline station, together with destruction efficiency data useful for design of such a treatment system. MTBE is a gasoline constituent that, in large measure because of its high solubility in water, is viewed as a widespread environmental problem and a potential threat to groundwater in several areas of the country (Lince et al, 2001;Squillace et al, 1998).The treatment of gasoline contamination in groundwater, and consequently of MTBE, has relied for the most part on the standard groundwater pump-and-treat system, often coupled with soil vapor extraction (SVE) or dual-phase extraction systems. In many of these remediation systems, the extracted groundwater is passed through virgin coconut carbon to adsorb MTBE and other dissolved gasoline constituents from the extracted groundwater so as to allow for the discharge of the treated water to sewer or stormwater runoff collection systems.…”
Section: Introductionmentioning
confidence: 99%